2017
DOI: 10.2217/fmb-2017-0041
|View full text |Cite
|
Sign up to set email alerts
|

Co-Production of NDM-1 and OXA-232 by ST16 Klebsiella Pneumoniae , Italy, 2016

Abstract: Carbapenem-resistant Klebsiella pneumoniae strains, New Delhi metallo-β-lactamase-1 producers, are still rare in Italy, being endemic in Southeast Asiatic region. In October 2016, a multidrug-resistant K. pneumoniae was isolated from blood and urine of an Italian long-hospitalized patient with urosepsis without travel history abroad. To the best of our knowledge, this is the first report of bacteremia caused by an ST16 K. pneuomoniae New Delhi metallo-β-lactamase-1 and OXA-232 co-producing carbapenemase, in It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 20 publications
1
33
0
Order By: Relevance
“…OXA-232 was first identified in France in 2013 from a K. pneumoniae isolate [9]. Since then, OXA232Kp have been discovered worldwide [10][11][12][13][14][15][16][17][18]. In this study, a nosocomial outbreak of epidemics OXA232Kp involving 61 patients was discovered in a teaching hospital in Shanghai, China.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…OXA-232 was first identified in France in 2013 from a K. pneumoniae isolate [9]. Since then, OXA232Kp have been discovered worldwide [10][11][12][13][14][15][16][17][18]. In this study, a nosocomial outbreak of epidemics OXA232Kp involving 61 patients was discovered in a teaching hospital in Shanghai, China.…”
Section: Discussionmentioning
confidence: 90%
“…In Europe and some Asia countries, the majority of OXA232Kp strains Fig. 1 The distribution of the OXA-232-producing K. pneumoniae isolates were ST14 and ST16 [10][11][12][13][14][15][16][17][18]. It has been confirmed that K. pneumoniae ST15 is the high-risk clones producing OXA-48, KPCs, CTX-M-15 and other ESBLs or carbapenemases.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Previous reports exist of NDM-5–, OXA-48–, and CTX-M-5–producing KP ST16 in Denmark, the United Kingdom, and Spain, respectively [ 26–28 ]. Scarce reports of isolated cases in the Netherlands (NDM-5) [ 29 ], Italy (NDM-1 and OXA-232) [ 30 ], and Rio de Janeiro, Brazil (OXA-370) were also documented [ 31 ]. In contrast, ST16 KP has rarely been described harboring bla KPC , except for 2 isolates reported in Rio de Janeiro in 2008 and 2009 ( bla KPC-2 ) and 1 isolate in Israel.…”
Section: Discussionmentioning
confidence: 99%
“…ST16 has been reported worldwide, showing different antimicrobial resistance profiles. In 2011, K. pneumoniae ST16 harbouring CTX-M-15 was the cause of nosocomial infections in Denmark and Sweden [4], NDM-5-carrying ST16 K. pneumoniae was described in Denmark [5], and later the co-presence of NDM-1 and OXA-232 in ST16 K. pneumoniae was observed in Italy [6].…”
Section: Introductionmentioning
confidence: 99%